The Implementation of Teaching Reading using Scientific Approach through WhatsApp at 9th Grade Junior High School - Lestari, Paujiah Rindi; Rizqiya, Rissa San (PROJECT (Professional Journal of English Education), 2025)
The purpose of this study is to analyze the implementation of teaching reading using a scientific approach through the Whatsapp application. The participants in this study were 9th grade students at one of the junior high schools in Parongpong. The research method used in this study was Qualitative research, and to obtain data, the instruments used in this study were lesson plan and questionnaire. The data of the research show that the implementation of teaching reading using scientific approach through WhatsApp application did not go well, where several difficulties arose such as the difficulty of students in accessing smartphones, students being overwhelmed by the number of assignments from several different class groups, and also the five stages of the scientific approach which took a lot of time. Then the results also show that the use of scientific methods can improve students' higher order thinking. Although the use of the WhatsApp application is widely used for learning due to the pandemic, there needs to be further research and solutions to overcome these shortcomings.